Early Failure of Dialysis Access among the Elderly in the Era of Fistula First - Woo, Karen (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: Recent evidence indicates that fistula maturation and patency may be compromised in the elderly dialysis population compared with younger patients. The objective of this study was to characterize the short-term outcomes of arteriovenous fistulas and arteriovenous grafts for hemodialysis access in the Medicare population. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This was a retrospective cohort study performed using Medicare Part A and B claims data from 2006 through 2011. The study population included 16,464 dialysis-dependent patients age ≥66 years undergoing arteriovenous fistula and arteriovenous graft creation. The primary outcome measure was incidence of repeat fistula/graft creation and tunneled catheter placements in the 12 months after arteriovenous fistula and graft creation. RESULTS: In the 12 months postindex fistula/graft, the mortality in the fistula group was 28.2% versus 29.9% in the graft group (P=0.03). A repeat fistula/graft creation was required in 26.9% of patients in the fistula group and 16.7% in the graft group (P<0.001). There was no significant difference in the proportion of patients who required a tunneled hemodialysis catheter in the 12 months after an index fistula creation (fistula 28.4% versus graft 27.3%, P=0.19). In the index fistula group, 44.4% of patients required a repeat fistula/graft creation and/or a tunneled catheter, compared with 33.7% in the graft group (P<0.001). At 365 days after the index fistula/graft, the repeat fistula/graft/catheter-free survival was 39.7% in the fistula group versus 46.0% in the graft group (P<0.001). Index fistula was associated with a higher risk of loss of repeat fistula/graft/catheter-free survival with an odds ratio of 1.19 (95% confidence interval, 1.13 to 1.24). CONCLUSIONS: Fistulas were associated with a somewhat lower mortality than grafts in the first 12 months after creation. However, the incidence of repeat fistula/graft creation and tunneled catheter placement is substantially higher in the first 12 months after fistula creation compared with grafts. One-year repeat fistula/graft/catheter-free survival is lower after fistula creation than grafts.